UNTOUCHABLE BEAUTY OF EVERYDAY AESTHETICS IN WIM WENDERS’ PERFECT DAYS - Fatmawati, Nindya Galuh; Saraswati, Agni (UI Scholars Hub, 2025)
Wim Wenders, in his latest film Perfect Days (2023), presents an everyday aesthetic experience conveyed through a visually striking aesthetic characterized by a